Factors influencing postgraduate students intention to use learning management system - Samaila, Kamaludeen; Md. Khambari, Mas Nida; Kumar, Jeya Amantha; Masood, Mona (University of Deusto, 2022)
Learning management systems (LMS) are continuously being implemented in tertiary institutions to manage and strengthen educational activities. LMS such as Moodle facilitates the management of learning content, collaboration, and communication. However, there have been limited studies examining factors influencing postgraduate students’ intention to use LMS in Malaysian universities, as studies mainly concentrate on undergraduates’ use intentions. Therefore, this study investigates factors influencing the behavioural intention to use LMS based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The results indicated performance expectancy (PE) followed by social influence (SI) and effort expectancy (EE) as the factors influencing the behavioural intention (BI) to use LMS. Concurrently, facilitating conditions (FC) were found not to influence BI, and we denote that socio-economy standings and maturity influence their overall acceptance of the LMS. Practical and theoretical implications are discussed accordingly.